The physiochemical properties of kefir using honey concentrations - Andi Padauleng Meliani Anwar; Fatma Maruddin; Farida Nur Yuliati; Jamyang Tashi Wangdi; Muhammad Ihsan Andi Dagong (jurnal1, 2021)
Kefir has a sour taste and distinctive aroma. This condition affects the level of consumer acceptance. The level of consumer acceptance of kefir can be improved by adding a sweetener, namely honey. This study aims to determine the characteristics of kefir made from commercial liquid milk to total lactic acid, pH value, viscosity, organoleptic (taste and preference) panelists to kefir with the addition of honey. This study used a completely randomized design (CRD). The treatment of this research was 4 honey concentrations (5%, 7%, 9% and without the addition of honey (0%) as a control) and was repeated 3 times. Kefir addition of honey is made in the following way: the liquid milk is sterilized at 105oC for 5 minutes and then the sterile milk is cooled down to a temperature of about 40oC. After chilling, sterile milk was inoculated with 3% (v/v) pre-propagated kefir starter and incubated at 37oC for 24 hours. Furthermore, kefir was added with honey treatment with a concentration of 5%, 7% and 9% (v/v) respectively and homogenized. Kefir honey is carried out in a series of tests including total lactic acid, acidity (pH), viscosity, organoleptic (taste and preference). The results showed that the different use of honey kefir did not change the lactic acid content. Increasing use of honey concentration causes pH value, viscosity, sweetness, and preference to increase. The best use of honey concentration in making kefir is 9%.